(3eMGSHI GdJcGdja (B:s (3eaGgje, eHGOF, JWHjbGJ (B/s - (3GdYfGJj, QVhGf eMeOs ((3YeGf(B: s (3OGQ UaGA(B, s, 2000)
(3ebOeI aj eMGSHI GdJcGdja, CfhGY GdJcGdja, YfGUQ GdJcGdja, bhGFe GdCYeGd, fXGe JcGdja ChGeQ GdJTZjd, fXGe JcGdja eQGMd GdJTZjd, fXQjGJ GdJcGdja, JWHjbGJ aj eMGSHI GdJcGdjas
(3GdeQGLY U(B.206s
Keywords: (3eMGSHI GdJcGdjas